Nanocrystalline growth activation energy of alumina polymorphs synthesised by mechanochemical technique. (August 2013) - Isfahani, T D; Javadpour, J; Khavandi, A; Rezaie, H R; Goodarzi, M
Abstract : Al2 O3 nanopowders were synthesised via mechanochemical method using AlCl3 and CaO as raw materials. The effect of thermal treatment on the structural evolutions and morphological characteristics of the nanopowders was investigated using X-ray diffractometry, transmission electron microscopy, scanning electron microscopy, differential thermal analysis and Rietveld refinement. The results showed that the average crystallite size of Al2 O3 was <100 nm up to ∼1200°C. The activation energy for Al2 O3 nanocrystallite growth during calcinations was calculated to be ∼22 598 and 30 195 J mol −1 for η - and κ -alumina respectively, while for α -Al2 O3, it was 8373 and 34 131 J mol −1 at temperatures up to 1200°C and >1200°C respectively. The mechanism of nanocrystalline growth of Al2 O3 polymorphs during annealing is also discussed.